2022
DOI: 10.3390/coatings12030340
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Texture on Total Energy Consumption of High Frequency Hydraulic Impact Piston Pair

Abstract: Limited by the influence of the traditional clearance seal structure on the leakage and friction loss of piston pair, the energy utilization ratio of the hydraulic impactor is difficult to improve effectively. To solve this problem, a novel micro-texture clearance seal structure of impact piston cylinder was proposed, and an integrated energy consumption evaluation index considering leakage and friction loss of impact piston pair was proposed. Based on the average Reynolds equation, a comprehensive energy cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Relevant studies have shown that the application of appropriate surface coating, appropriate surface texture, and the use of low viscosity lubricating oil and additives on the surface of the friction pair can reduce the friction loss by more than 60% during the long-term use of the friction pair (15-20 years) [15]. Therefore, surface texture has been widely used in cutting tools [16], plain bearings [17], internal combustion engines [18], plunger pumps [19], hydraulic cylinders [20], and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies have shown that the application of appropriate surface coating, appropriate surface texture, and the use of low viscosity lubricating oil and additives on the surface of the friction pair can reduce the friction loss by more than 60% during the long-term use of the friction pair (15-20 years) [15]. Therefore, surface texture has been widely used in cutting tools [16], plain bearings [17], internal combustion engines [18], plunger pumps [19], hydraulic cylinders [20], and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…Although the structure of the slippers seems simple, its operation mechanism is complex. A lot of researchers focus on the boundary of velocity, pressure, and temperature as well as the profile of the running surface [1][2][3][4][5][6]. Based on the ideal rigid sealing land, the dynamic characteristics of the sliding pair were theoretically and experimentally analyzed by Harris [7]; there is a significant difference between the results of experimental and theoretical under the condition of large tilt angles [8].…”
Section: Introductionmentioning
confidence: 99%